Induction Motor Speed Control Using Indirect Z-source Matrix Converter with PSO-PI Controller under Various Break Conditions - Majid Salim; Mohammad Sarvi (Institute of Advanced Engineering and Science, 2013)
Since induction motors are preferred over direct current machines in the view of cost and simplicity, they have widely been used in industry. In this paper, the speed of the three-phase induction motor has been controlled using an indirect z-source matrix converter. The method used for this purpose is flux control keeping the V/f ratio and regulating slippage. The effect of flux changes and reference velocity in this method has been taken into consideration and various electric break methods on the motor have been studied accordingly. Coefficients of PI controllers have been obtained in the proposed system for desirable response by PSO Algorithm. The proposed system with the respective converter has been simulated in SIMULINK environment using the information of an induction machine by MATLAB Software. The results show to using the proposed system and indirect z-source matrix converter, appropriate velocity and desirable torque are obtained in a short time. DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1783